Determinasi Nilai Perusahaan: Peran Profitabilitas, Firm size, Eco-Efficiency dan Kinerja Lingkungan pada Sektor Basic Materials - Arum Puspita Anggraini; Feny Fidyah; Afrila Eki Pradita; Astried Permanasari; Irwandaru Dananjaya (Journal of Business and Economics Research (JBE), 2026)
This study aims to analyze the effect of Return on Assets (ROA), Firm Size, Eco-efficiency, and Environmental Performance on Firm Value in basic materials sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Firm value is an important indicator that reflects investors' perceptions of a company's performance and future prospects. In the context of increasing attention to sustainability issues, both financial and non-financial factors, such as eco-efficiency and environmental performance, have become important aspects to examine in relation to firm value. This study employed a quantitative approach using an associative research method. The population consisted of all basic materials sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The sample was selected using a purposive sampling technique based on predetermined criteria, resulting in a number of companies that met the requirements as research samples. The study utilized secondary data obtained from annual reports, sustainability reports, and the official website of the Indonesia Stock Exchange. Data analysis was conducted using multiple linear regression with the assistance of the Statistical Product and Service Solutions (SPSS) software. The results indicate that Return on Assets (ROA), Firm Size, and Eco-efficiency have a positive and significant effect on Firm Value. These findings suggest that a company's ability to generate profits, its larger size, and the implementation of environmental efficiency practices can enhance investor confidence and increase firm value. Meanwhile, Environmental Performance has a negative and significant effect on Firm Value, indicating that improvements in environmental performance, which often require substantial short-term costs, may reduce investors' perceptions of firm value. These findings imply that companies need to maintain a balance between achieving strong financial performance and implementing sustainability practices in order to enhance firm value. This study provides an empirical contribution by integrating financial factors and environmental sustainability factors in explaining firm value in the basic materials sector. Therefore, the findings are expected to serve as a reference for corporate management, investors, and future researchers in understanding the determinants of firm value from both financial and sustainability perspectives.